Genetic Variants in Circadian Rhythm Genes and Self-Reported Sleep Quality in Women with Breast Cancer. Issue 1 (1st July 2019) - LeVan, Tricia D.; Xiao, Peng; Kumar, Gaurav; Kupzyk, Kevin; Qiu, Fang; Klinkebiel, David; Eudy, James; Cowan, Kenneth; Berger, Ann M.
Introduction: Women diagnosed with breast cancer (BC) are at increased risk of sleep deficiency. Approximately 30–60% of these women report poor sleep during and following surgery, chemotherapy, radiation therapy, and anti-estrogen therapy. The purpose of this study was to examine the relationship between genetic variation in circadian rhythm genes and self-reported sleep quality in women with BC. Methods: This cross-sectional study recruited women with a first diagnosis of breast cancer at five sites in Nebraska and South Dakota. Sixty women were included in the study. Twenty-six circadian genes were selected for exome sequencing using the Nextera Rapid Capture Expanded Exome kit. 414 variants had a minor allele frequency of ≥5% and were included in the exploratory analysis. The association between Pittsburgh Sleep Quality Index (PSQI) score and genetic variants was determined by two-sample t-test or ANOVA. Results: Twenty-five variants were associated with the PSQI score at p < 0.10, of which 19 were significant at p<0.05, although the associations did not reach statistical significance after adjustment for multiple comparisons. Variants associated with PSQI were from genes CSNK1D & E, SKP1, BHLHE40 & 41, NPAS2, ARNTL, MYRIP, KLHL30, TIMELESS, FBXL3, CUL1, PER1&2, RORB. Two genetic variants were synonymous or missense variants in the BHLHE40 and TIMELESS genes, respectively. Conclusions: These exploratory results demonstrate an association of genetic variants in circadian rhythm pathways with self-reported sleep in women with BC. Testing this association is warranted in a larger replication population.